Comparative Study of Different 2D Roof Truss Design - Mounika, L; mounika, p (The journal of contemporary issues in business and government, 2020)
For decades, the construction industry has relied on structural steel, a resilient material that can be moulded into any shape requested to achieve a project’s final and attractive look. In addition to Type, Pratt, Howe and Warren types of steel trusses, there are many additional options available. They are also available in a variety of sections, such as tubular, square, and rectangular hollow. The Warren type, the Howe type, and other truss types are examined side by side in this work. There have been no delays in the building of Pratt and K-type trusses with a 36-meter span and varied heights. Rather of using solid pieces, hollow components are employed in their place. Some of the parts that are commonplace Stad pro v8i software is utilised to conduct the research. According to the results of this comparison, it will be established that the most cost- effective steel truss structures are those with the lowest prices and lightest weight.